2008
DOI: 10.1249/mss.0b013e31815a95a7
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Tolerance and Thermoregulatory Responses during Cycling in Boys and Men

Abstract: This study failed to reveal differences in exercise tolerance, thermoregulatory adaptation, or cardiovascular response to exercise in the heat between euhydrated prepubertal boys and adult men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…It is known that any type of stress causes disruption of homeostasis and an imbalanced antioxidant status in several organs [9]. In this study we used cold as an acute stressing agent, considering that when exposed for long term (more than 1 month) it is observed an adaptation mechanism [10][11][12]. According to Janský et al [13], the chronic exposure to extreme low temperatures would not decrease cardiomyocytes nuclear size such as we found in our study due to the adjustment condition.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that any type of stress causes disruption of homeostasis and an imbalanced antioxidant status in several organs [9]. In this study we used cold as an acute stressing agent, considering that when exposed for long term (more than 1 month) it is observed an adaptation mechanism [10][11][12]. According to Janský et al [13], the chronic exposure to extreme low temperatures would not decrease cardiomyocytes nuclear size such as we found in our study due to the adjustment condition.…”
Section: Discussionmentioning
confidence: 99%
“…Davies et al found that thermoregulation was identical when cycling to exhaustion in hot (∼31°C) or cold (∼19°C) controlled environments. 18 In a climate-controlled room, Cramer et al showed that changes in T co during 60 minutes of cycling at an exercise intensity eliciting 9.0 W·kg −1 of metabolic heat production T co , core body temperature; VO 2max , maximum oxygen uptake; VT1, first ventilatory threshold.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…However, more recent studies, in which tighter controls have been employed to match relative exercise intensities, fitness levels, environmental conditions and hydration status, indicate that children and adults have similar capacity to deal with thermal loads and exercisetolerance time during exercise in the heat (Inbar et al 2004;Rowland et al, 2008;Shibasaki et al, 1997). What is evident is that the mechanisms by which young individuals dissipate heat loads during exercise differ from those of adults (Falk & Dotan, 2008;Rowland, 2008).…”
Section: Fluid Recommendations For Adolescent Athletesmentioning
confidence: 99%